2014
DOI: 10.1515/zkri-2013-1684
|View full text |Cite
|
Sign up to set email alerts
|

In-situ high-pressure X-ray diffraction on the Zn6Sc 1/1 periodic cubic approximant to a quasicrystal

Abstract: The Zn 6 Sc 1 / 1 cubic approximant to a quasicrystal has been studied in-situ at high pressures by single-crystal X-ray diffraction. This phase can be described as a bcc packing of Tsai-type icosahedral clusters whose center is occupied by a disordered Zn 4 tetrahedron. At ambient pressure the Zn 6 Sc undergoes a structural phase transition at 159 K to a monoclinic superstructure in which the Zn 4 tetrahedra are orientationally ordered along the [ 101] direction of the high-temperature bcc phase. In the press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Now, we focus on experimental observations. Although all of the superstructures under high pressure are still unsolved, LT x-ray and electron diffraction studies under both ambient and high pressure indicate that ordered tetrahedra form commensurate superlattices in all cases [5,8,11,12] (see also table 1), which is in agreement with the Lifshitz condition. There are two types of LT superstructures reported in the literature that consist of fully ordered tetrahedra, Cd 6 Ce (Pn3) [17,18] and Cd 6 M [5] (M = Ca, Y, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Tm) (Zn 6 Sc) [8] (C2/c), which are now successfully explained by {k} = H(100)A u and N(1/2 0 1/2)A u , respectively, in table 2 and a second-order transition is allowed in both cases.…”
Section: Comparison With the Observed Superstructuressupporting
confidence: 65%
See 2 more Smart Citations
“…Now, we focus on experimental observations. Although all of the superstructures under high pressure are still unsolved, LT x-ray and electron diffraction studies under both ambient and high pressure indicate that ordered tetrahedra form commensurate superlattices in all cases [5,8,11,12] (see also table 1), which is in agreement with the Lifshitz condition. There are two types of LT superstructures reported in the literature that consist of fully ordered tetrahedra, Cd 6 Ce (Pn3) [17,18] and Cd 6 M [5] (M = Ca, Y, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Tm) (Zn 6 Sc) [8] (C2/c), which are now successfully explained by {k} = H(100)A u and N(1/2 0 1/2)A u , respectively, in table 2 and a second-order transition is allowed in both cases.…”
Section: Comparison With the Observed Superstructuressupporting
confidence: 65%
“…However, as shown in table 2, a second-order transition to a non-cubic phase such as that reported is not possible in this case, which means that the transition is first-order. The recently reported fourfold pseudo-cubic lattice in Zn 6 Sc [12] cannot be obtained directly from I m 3 by a secondorder transition, because the Lifshitz condition is not satisfied for k points inside the Brillouin zone, except for point . Therefore, many observed superstructures are allowed by a second-order transition whereas some are not, which implies the existence of a first-order transition as well.…”
Section: Comparison With the Observed Superstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although turn-key solutions for the in-laboratory measurement of physical properties under combined LT/HP conditions are readily commercially available (for example in the case of Quantum Design's MPMS/PPMS devices equipped with pressure cells), XRD measurements under the same conditions are still an expert topic and usually limited to diffractometers at specialized synchrotron beamlines (Gerard & Pernolet, 1973;Morosin & Schirber, 1974;Chasseau et al, 1993;Tang et al, 1998;Ohwada et al, 2001;Takemura et al, 2002;Suzuki & Endo, 2003;Guionneau et al, 2004;Yoshimura et al, 2006;Bizen et al, 2008;Zimmermann et al, 2008;Mittal et al, 2011;Shepherd et al, 2011;Li et al, 2012;Tse et al, 2012;Cameron, 2014;Yamada et al, 2014;Hejny & Minkov, 2015;Elatresh et al, 2017;Shen & Mao, 2017;Povedano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of quasicrystals has been examined as a function of temperature, of pressure, and of temperature and pressure Yamada et al, 2014). Although quasicrystals are not close-packed structures and hence phase transitions are expected at high pressure, they show remarkably stable behaviour, with the only reported pressure-induced phase transitions being in i-AlLiCu and in the Zn 6 Sc approximant to a quasicrystal (Yamada et al, 2014). In no other high-pressure study of quasicrystals has a phase transition been observed in the investigated pressure range of up to 70 GPa.…”
Section: High-pressure Crystallography Of Aperiodic Crystalsmentioning
confidence: 99%